PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Subsektor Transportasi yang Terdaftar di BEI Tahun 2018-2021) - Vivi Mardahlia; Imam Ghozali (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of good corporate governance (GCG) on financial distress. The independent variables in this study are gender diversity on board, institutional ownership, managerial ownership, proportion of independent commissioners, number of directors, and audit committee size. The dependent variable used in this study was financial distress. This study uses secondary data from the financial statements of companies listed on the Indonesia Stock Exchange. The purposive sampling method was used in this research so that 114 samples were obtained from transportation sector companies that published their financial statements in 2018-2021. This study used logistic regression analysis method to test Good Corporate Governance for financial distress. The results showed that gender diversity on board, institutional ownership, and proportion of independent commissioners had a negative influence on financial distress. Meanwhile, managerial ownership, number of directors, and audit committee size do not have a significant effect on financial distress.